2020
DOI: 10.1200/jco.19.01882
|View full text |Cite
|
Sign up to set email alerts
|

Results of a Multicenter Phase II Study of Atezolizumab and Bevacizumab for Patients With Metastatic Renal Cell Carcinoma With Variant Histology and/or Sarcomatoid Features

Abstract: PURPOSE In this multicenter phase II trial, we evaluated atezolizumab combined with bevacizumab in patients with advanced renal cell carcinoma (RCC) with variant histology or any RCC histology with ≥ 20% sarcomatoid differentiation. PATIENTS AND METHODS Eligible patients may have received previous systemic therapy, excluding prior bevacizumab or checkpoint inhibitors. Patients underwent a baseline biopsy and received atezolizumab 1,200 mg and bevacizumab 15 mg/kg intravenously every 3 weeks. The primary end po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
84
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(87 citation statements)
references
References 24 publications
3
84
0
Order By: Relevance
“…Combination regimens containing ICIs became the standard of care for patients with mRCC based on phase 3 clinical trials conducted mainly in clear cell tumors (17). The same or similar combinations are being investigated in nonclear cell histologies, and emerging data are promising (18). Yet, not all patients will be considered eligible for those regimens.…”
Section: Discussionmentioning
confidence: 99%
“…Combination regimens containing ICIs became the standard of care for patients with mRCC based on phase 3 clinical trials conducted mainly in clear cell tumors (17). The same or similar combinations are being investigated in nonclear cell histologies, and emerging data are promising (18). Yet, not all patients will be considered eligible for those regimens.…”
Section: Discussionmentioning
confidence: 99%
“…Individual case reports and the subgroup analysis of the ipili­mumab plus nivolumab and axitinib plus pembrolizu­mab pivotal studies show a promising response in nccRCC and especially those with sarcomatoid features [11, 20-22]. Initial data are also available for the combination of bevacizumab and atezolizumab [23]. The current ESMO guidelines therefore consider the IO/IO combination to be a good therapy option for sarcomatoid RCCs [24].…”
Section: Discussionmentioning
confidence: 99%
“…NCCRCC accounts for ~20% of kidney cancer, with papillary, chromophobe and sarcomatoid variants accounting for the majority of subtypes 5 .For advanced NCCRCC, the only treatment options, which have been largely extrapolated from agents studied in CCRCC, include antiangiogenics or mTOR inhibitors. However, several large studies have demonstrated that patients with NCCRCC have a worse prognosis with lower response rates to these therapies [9][10][11][12][13][14][15][16] .…”
Section: Discussionmentioning
confidence: 99%
“…papillary, chromophobe, sarcomatoid) have an intact VHL gene, and are broadly classified as non-clear cell RCC (NCCRCC). NCCRCC show minimal responses to antiangiogenics and have no effective treatment options [9][10][11][12][13][14][15][16] .While recent advances in immunotherapeutic approaches have further improved outcomes for metastatic CCRCC, standard therapies for advanced NCRRCC are lacking and long-term survival is poor 4 .…”
Section: Introductionmentioning
confidence: 99%